The impact of perceived stress on school adjustment among Chinese boarding students in rural junior high school: a moderated mediation model of teacher support and self-esteem - Jiang, Yuqin; Zhang, Lyuci; Govindasamy, Priyalatha; Mohd Isa, Nor Junainah; Zaremohzzabieh, Zeinab; Roslan, Samsilah; Che Amat, Muhammad Asyraf; Puad Mohd Kari, Dharatun Nissa; Du, Lifeng (Routledge, 2025)
Boarding students in rural junior high schools often face challenges in adjusting to school life, making it crucial to understand the factors influencing their adjustment. This study explores the relationship between perceived stress and school adjustment among 818 boarding students in Guangxi (375 males, 443 females) and investigates the role of teacher support and self-esteem in this dynamic. Results showed a significant negative correlation between perceived stress and school adjustment. Teacher support partially mediates this relationship, suggesting that supportive teachers can mitigate stress-related adjustment difficulties. Moreover, self-esteem negatively moderates the initial stage of this mediation, indicating that students with higher self-esteem experience less stress-related disruption. These findings underscore the importance of strengthening teacher support and fostering students’ self-esteem to improve school adjustment outcomes. This research offers valuable insights into the interplay of stress, teacher support, self-esteem, and school adjustment, informing targeted interventions for boarding students.